Analysis of the Level of Difficulty and Differentiating Power of the Final Semester Assessment Made by Teachers of Class XI High School Chemistry Subjects in Cirebon in the Odd Semester of the 2022/2023 School Year - Nurdiyanti, Dewi; Nurlia Hermawati, Tania; Dwi Cahyani, Mutiara (Jurnal Edusci, 2024)
This study aims to determine the quality on the Odd Semester Final Assessment (PAS) of Grade XI Chemistry Subjects in SMAs in the Cirebon Region for the 2022/2023 Academic Year. This research is a quantitative description research with data collection methods using document analysis to obtain data. The sample of this study was grade XI students. Quantitative research was conducted with the help of the ANATES software program version 4.09. the results showed: (1) In terms of Distinguishing Power, the highest value is in school E (77%) and the lowest value is school C (50%). (2) In terms of Level of difficulty there is a proportional comparison in school B with a ratio of 3:5:2.